NICC - null (IEE Colloquium on How to Compete and Connect: Understanding the Engineering of Telecommunications Network Interconnection, 1997)
This study aimed to evaluate the psychometric properties of the Arabic Critical Care Nursing Motivation Scale. Following adequate translation methods, the scale was administered to a convenient sample of 241 participants. The Kaiser-Meyer-Olkin value was 0.90 and the Bartlett sphericity test was significant (χ 2 = 3319.277, p < 0.001), indicating its suitability for EFA. The total variance explained was 64.318%. CFA fit indices were at acceptable levels and a Cronbach's alpha of 0.92. The mean of Motivation scale was 100.48 (SD = 14.80) where lower scores indicate higher motivation. The mean score of subcategories of the scale was 44.65 (SD = 7.45), 11.96 (SD = 3.67), 23.58 (SD = 4.26), 20.29 (SD = 3.26) for job attributions, remuneration, co-worker, and achievements respectively. The analysis showed the Arabic version of the motivation scale to be valid and reliable with exceptionally low scores among the Lebanese sample which highlight the need for interventions targeting remuneration and workplace resources to improve retention. Tackling motivational concerns in resource-constrained environments is essential, where nurses encounter considerable obstacles because of the workplace conditions such as resource constraints. In addition, examining the connection between motivation and job satisfaction among nurses in Lebanon could uncover potential interventions to enhance both of these factors, which could ultimately help alleviate the nursing shortage.